Competitiveness and technological capital as determining factors of exports in small and medium-sized companies - Gladys Rueda-Barrios; Gladys Mireya Valero Cordoba; Jairo Gonzalez-Bueno (Problems and Perspectives in Management, 2023)
This study explores international business integration, focusing on Colombian small and medium-sized enterprises (SMEs). It delves into the crucial aspects of competitiveness and technological capital influencing the export models of these SMEs. Using a questionnaire, responses were gathered from 63 Colombian SMEs exporting to 74 countries with 333 tariff positions. This analysis examines competitiveness factors like innovation, productivity, and business structure, as well as technological capital components such as R&D management, technological processes, and equipment, all tailored to the context of Colombian SMEs. The findings establish a comprehensive model elucidating direct and indirect relationships among these variables. They underscore the importance of strengthening competitiveness elements, particularly the infusion of technology into process and product innovation, alongside productivity and business structure rooted in the value derived from information technologies. Simultaneously, the study highlights the importance of nurturing employees’ physical, financial, and language skills within Colombian SMEs. This study accentuates the pivotal role of investment in technological capital aspects, including research and development management, personnel, and leveraging information technology, especially within Colombian SMEs. These investments are instrumental in augmenting performance and ensuring success in the international business arena. The paper contributes to both theoretical understanding and practical applications in enhancing the international competitiveness of Colombian SMEs.